Macroeconomics - Larraín B., Felipe, (The MIT Press essential knowledge series, 2020)
"Macroeconomics is the study of the economic attributes (including the performance, structure, behavior, and decision-making) of whole systems. Macroeconomists study changes in the aggregate, collecting data on unemployment, growth, inflation, income, saving and spending, trade, and other aspects of regional, national, and international economic life. Policymakers depend on macroeconomists' knowledge of the main elements and basic forces that govern each country's economy and the global economy when making decisions about taxes, industry regulations, trade terms and policies, and more. These decisions in turn affect decisions made by individuals and businesses, especially in a globalized world. This entry into the Essential Knowledge series covers such topics as GDP and its relation to the welfare of people; why some countries grow strongly while others stagnate; the challenges of the labor market in the twenty-first century; the money market and the inflation rate; the implications of having different exchange rate systems -fixed, pegged, bands, floats; household consumption and savings decisions; investment decisions; the current account of the balance of payments; government budgets, taxes and fiscal policy; and the debate on globalization. The book addresses the causes and consequences of recent economic crises like the subprime crisis and Euro crisis. This book draws on examples from economies around the world. Given the author's professional experience as minister of finance for Chile, many examples are drawn from Latin America, but also Asia, Africa, Europe, and the United States"--